Autophagy reprogramming stem cell pluripotency and multiple-lineage differentiation. Issue 6 (10th June 2022) - Yang, Yi-Ping; Lai, Wei-Yi; Lin, Tzu-Wei; Lin, Yi-Ying; Chien, Yueh; Tsai, Yi-Ching; Tai, Hsiao-Yun; Wang, Chia-Lin; Liu, Yung-Yang; Huang, Pin-I; Chen, Yi-Wei; Lo, Wen-Liang; et al.
Abstract : The cellular process responsible for the degradation of cytosolic proteins and subcellular organelles in lysosomes was termed "autophagy." This process occurs at a basal level in most tissues as part of tissue homeostasis that redounds to the regular turnover of components inside cytoplasm. The breakthrough in the autophagy field is the identification of key players in the autophagy pathway, compounded under the name "autophagy-related genes" (ATG) encoding for autophagy effector proteins. Generally, the function of autophagy can be classified into two divisions: intracellular clearance of defective macromolecules and organelles and generation of degradation products. Therapeutic strategies using stem cell–based approach come as a promising therapy and develop rapidly recently as stem cells have high self-renewability and differentiation capability as known as mesenchymal stem cells (MSCs). They are defined as adherent fibroblast-like population with the abilities to self-renew and multi-lineage differentiate into osteogenic, adipogenic, and chondrogenic lineage cells. To date, they are the most extensively applied adult stem cells in clinical trials. The properties of MSCs, such as immunomodulation, neuroprotection, and tissue repair pertaining to cell differentiation, processes to replace lost, or damaged cells, for aiding cell repair and revival. Autophagy has been viewed as a remarkable mechanism for maintaining homeostasis, ensuring the adequate function and survival of long-lived stem cells. In addition, authophagy also plays a remarkable role in protecting stem cells against cellular stress when the stem cell regenerative capacity is harmed in aging and cellular degeneration. Understanding the under-explored mechanisms of MSC actions and expanding the spectrum of their clinical applications may improve the utility of the MSC-based therapeutic approach in the future.